Three-dimensional evaluation of the root resorption of maxillary incisors after the orthodontic traction of bicortically impacted canines: case reports - Luis Ernesto Arriola-Guillén; Yalil Augusto Rodríguez-Cárdenas; Gustavo Armando Ruíz-Mora; Aron Aliaga-Del Castillo; Juan Schilling; Heraldo Luis Dias-Da Silveira (SpringerOpen, 2019)
Abstract Background The root resorption of the maxillary incisors after the orthodontic traction of impacted canines is a concern for clinicians. The aim of this case series report was to evaluate the root resorption of the maxillary incisors after traction until the occlusal plane of the bicortically impacted canines (placed between the two cortical bones in the middle of the alveolar process) located in a complex position using three-dimensional superimposition. This case series report describes the root resorption of the maxillary incisors after orthodontic traction with NiTi closed coil springs and a heavy anchorage appliance in three cases of bilateral impacted canines located in a complex position (bicortically) near to midline. Cone-beam computed tomographies (CBCTs) were obtained before and after traction. Root resorption in all root surfaces of the maxillary incisors was evaluated with color-coded maps using the ITK-SNAP and the 3D Slicer software to indicate loss of the root surface (in red) or gain of the surface (in blue) and was quantified in millimeters by the superimposition method. Results The root changes mainly occurred in the apical third of the maxillary incisor root and did not exceed 2 mm. Conclusions Root resorption of the maxillary incisors after the traction of bicortically impacted canines located in a complex position was observed mainly in the apex region, and the amount of root resorption was smaller than 2 mm in all root surfaces.